Postnatal ontogenesis of the circadian clock within the rat liver - Sládek, Martin; Jindráková, Zuzana; Bendová, Zdeňka; Sumová, Alena (American journal of physiology. Regulatory, integrative and comparative physiology, 2007)
In mammals, the circadian oscillator within the suprachiasmatic nuclei (SCN) entrains circadian clocks in numerous peripheral tissues. Central and peripheral clocks share a molecular core clock mechanism governing daily time measurement. In the rat SCN, the molecular clockwork develops gradually during postnatal ontogenesis. The aim of the present work was to elucidate when during ontogenesis the expression of clock genes in the rat liver starts to be rhythmic. Daily profiles of mRNA expression of clock genes Per1, Per2, Cry1, Clock, Rev-Erbalpha, and Bmal1 were analyzed in the liver of fetuses at embryonic day 20 (E20) or pups at postnatal age 2 (P2), P10, P20, P30, and in adults by real-time RT-PCR. At E20, only a high-amplitude rhythm in Rev-Erbalpha and a low-amplitude variation in Cry1 but no clear circadian rhythms in expression of other clock genes were detectable. At P2, a high-amplitude rhythm in Rev-Erbalpha and a low-amplitude variation in Bmal1 but no rhythms in expression of other genes were detected. At P10, significant rhythms only in Per1 and Rev-Erbalpha expression were present. At P20, clear circadian rhythms in the expression of Per1, Per2, Rev-Erbalpha, and Bmal1, but not yet of Cry1 and Clock, were detected. At P30, all clock genes were expressed rhythmically. The phase of the rhythms shifted between all studied developmental periods until the adult stage was achieved. The data indicate that the development of the molecular clockwork in the rat liver proceeds gradually and is roughly completed by 30 days after birth.
Keywords: časové faktory; Pregnancy; Rats; RNA, Messenger; novorozená zvířata; Circadian Rhythm; Gene Expression Regulation, Developmental; játra; Financing, Organized; Animals; Animals, Newborn; Liver; zvířata; cirkadiánní rytmus; Biological Clocks; Time Factors; financování organizované; krysa rodu Rattus; biologické hodiny; messenger RNA; ženské pohlaví; těhotenství; Female; vývojová regulace genové exprese